PENGGUNAAN MEDIA POSTER DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI DI SDN 223 SUMPANG MINANGAE - Sulaeman, Sulaeman; Yuliani, Yuliani; Asvika, Ayu (IAIN Bone, 2023)
The implementation of learning media in the form of posters to enhance students' interest in Islamic Education (PAI) subject at SDN 223 Sumpang Minangae is the focus of this research. The objective of this study is to improve students' learning interest in PAI by utilizing poster media. The research adopts the method of Classroom Action Research (CAR) and is conducted in two cycles. Cycle I took place on November 12, 2022, and Cycle II on November 19, 2022, at SDN 223 Sumpang Minangae, located in Sumpang Minangae Village, Sibulue District, Bone Regency, South Sulawesi Province. The research subjects are 19 sixth-grade students, comprising 13 female students and 6 male students. Data collection techniques include observation, interviews, and documentation. The data obtained are analyzed using descriptive quantitative analysis. The results of the research indicate a noticeable increase in students' learning interest after the implementation of poster media in PAI learning during both Cycle I and Cycle II. The indicators for this improvement are: a sense of enjoyment during learning, increased interest in learning, and a higher level of attentiveness in learning, reaching up to 95%. Therefore, it can be concluded that the implementation of poster media has led to an improvement in students' learning interest in the PAI subject for the sixth-grade students of SDN 223 Sumpang Minangae.Â Keywords: Studentâ€™s Learning Interest, Poster Media Session, Islamic Education